Data action using data for public good - Williams, Sarah 1974- (The MIT Press, 2020)
"Data Action will offer a model for reading, collecting, visualizing, and putting data to work on civic change. Using arresting graphics and influential case studies, as well as incorporating cultural and historical context, Data Action presents a helpful corrective to standard practice. Historically, data has been used and manipulated to make policy decisions without input from the general public. Data Action asks advocates of big data to rethink how they work by laying out a methodology for more transparent and accountable data analysis. The tools outlined in this book will help anyone, not just government officials, but data scientists, civic activists and hackers, as well as all citizens reaching for more effective civic debates and policy reforms, to shape our environment, economy, public health, and quality of life, with greater transparency and democratic participation"--
Keywords: Politik; Öffentlichkeit; Ethik; Big Data; Verwaltung; Public administration / Data processing; Information behavior; POLITICAL SCIENCE / Public Affairs & Administration